Qualität der Hochschullehre - Markus Prandini; Claudia Bornemeyer; Immanuel Ulrich (IUBH Internationale Hochschule, 2021)
– The starting point of this paper is the ongoing discussion among academics and practitioners on how to define qualityin university teaching. The different perspectives of the Humboldtian model of higher education, the fields of university didactics and quality management are brought together in a definition of "good teaching" in higher education. With reference to John Hattie's seminal study, five quality factors are proposed for higher education teaching: quality of the (1) curriculum, (2) didactics and methodology of teaching, (3) learning media, (4) performance assessment, and (5) student support. These factors have to be implemented in different forms of study: on campus studies, distance learning, dual studies and part-time studies. Due to the special characteristics of each of these forms, different challenges arise.Quality management in teaching also has to consider in how far the objectives of good university teaching have been achieved in a given situation. Four levels of measurement - reaction, learning, behaviour and results - clarify the distinction between output (direct and immediate results) and outcomes (long-term effects) of university teaching.The discussion of what teaching quality in higher education really means will remain a "hot topic". Continuous changes in society ensure that the discussion must go on.Especially the ongoing developments in digitalization will give new ground for this discussion. The common denominator is that high quality teaching should provide students with the competencies required for their future professional and personal life.
Keywords: A22; A23; 650; Qualität der Hochschullehre; Hochschuldidaktik; Kompetenzförderung